Mn (II) complexes based on oligopyridines: structure, thermal studies and optical band-gap determination. (1st March 2016) - Alghool, Samir; Slebodnick, Carla
Two cationic complexes [Mn(II)(terpy)2]·2(PCP) and [Mn(II)(dipy)3]·2(PCP) (terpy = 2, 2':6', 2''-terpyridine) (dipy = 2, 2-dipyridyl) (PCP = pentacyanopropenide) have been synthesised. Single crystal X-ray diffraction revealed that the PCP ligand acts as a counter ion. The thermal stability of these compounds was investigated. Optical absorption measurements show that the fundamental absorption edge obeys Tauc's relation for the allowed non-direct transition. The optical band gap (Eg) values equal ∼2.7 eV for both complexes.